Relationship between Fetal Station and Successful Vaginal Delivery in Nulliparous Women - Segel, Sally Y.; Carreño, Carlos A.; Weiner, Steven J.; Bloom, Steven L.; Spong, Catherine Y.; Varner, Michael W.; Rouse, Dwight J.; Caritis, Steve N.; Grobman, William A.; Sorokin, Yoram; Sciscione, Anthony; Mercer, Brian M.; Thorp, John M.; Malone, Fergal D.; Harper, Margaret; Iams, Jay D.; null (American Journal of Perinatology, 2012)
Objective To study the relationship between fetal station and successful vaginal delivery in nulliparous women.Study Design This was a secondary analysis from a previously reported trial of pulse oximetry. Vaginal delivery rates were evaluated and compared with respect to the fetal station. Spontaneous labor and induction of labor groups were evaluated separately. Multivariable logistic regression analysis was performed to adjust for confounding factors.Results Successful vaginal delivery was more frequent with an engaged vertex for spontaneous labor (86.2% versus 78.6%; p = 0.01) and induced labor (87.7% versus 66.1%; p < 0.01). After adjustment, engaged fetal vertex was not associated with vaginal delivery for spontaneous labor (odds ratio [OR] 1.5; 95% confidence interval [CI] 0.95 to 2.3; p = 0.08) or for women with induced labor (OR 2.2; 95% CI 0.96 to 5.1; p = 0.06).Conclusion Among nulliparous women enrolled in the FOX randomized trial in spontaneous labor or for labor induction, an engaged fetal vertex does not affect their vaginal delivery rate.
Keywords: labor; fetal station; vaginal delivery